PLANNING AND MANAGEMENT OF THE ORGANIZATION THROUGH THE USE OF STRATEGIC METHODS AND MATRIX MODELS - Melnyk, T. S.; Khrystofor, O. V. (Science and Transport Progress, 2008)
In the article existing views on the role of strategy in an organization management are considered, an authors’ interpretation of practical application of one of methods for determining the strategic goals of organization is given, the strategic planning levels are selected, a systematization of matrices used in analysis of strategic alternatives is conducted, and stage-by-stage introduction of matrix approach into1 the strategic planning process is suggested.